Effects of Intradermal Sterile Water Injections in Women with Low Back Pain in Labor: A Randomized, Controlled, Clinical Trial - DEMİRCİ, NURDAN (GALENOS YAYINCILIK, 2018)
Background: In addition to the pain caused byuterine contractions during labour, continuous and severe back pain is observed in 33% of women. Several pharmacological and nonpharmacological methods are available for managing this pain. Sterile water injection is considered as alternative method for nonpharmacological pain management. Aims: To assess the satisfaction level and effectiveness of sterile water injection for back pain among women in labour. Study Design: Randomized controlled trial. Methods: A total of 168 term, healthy women with labour pain and severe back pain were randomized into the sterile water injection (study) and dry injection (placebo) groups. Injections were applied to the rhombus of Michaelis in the sacral area. Pain scores were assessed at 10, 30, 60, 120, and 180 min using a visual analogue scale. Additionally, the need for epidural analgesia, Apgar score, mode of delivery, time of delivery, maternal satisfaction, and breastfeeding score were assessed. Results: The mean back pain scores at 30 min after injections were significantly lower in the study group (study group: 31.66 +/- 11.38; placebo: 75 +/- 18.26, p<0.01). The mean decrease in pain scores after 30 min according to baseline was significantly higher in the study group (study group: 54.82 +/- 7.81; placebo: 13.33 +/- 12.05, p<0.01). The need for epidural analgesia, time of delivery, mode of delivery, and Apgar and breastfeeding scores were similar in both groups. Maternal satisfaction from the analgesic effect was significantly higher in the study group (study group: 84.5%; placebo: 35.7%, p<0.01). Conclusion: The application of sterile water injection is effective for relieving back pain in the first stage of labour and has a sufficient satisfaction level among women.
Keywords: Analgesia; injections; labor; obstetrical; pain; randomized controlled trial; INTRACUTANEOUS INJECTIONS; RELIEF